one more question

archana.ved

New member
Joined
Feb 5, 2014
Messages
7
if -1 ≤ x ≤ 2 and 1 ≤ y ≤ 3 then least positive value of (2y -3x) is

suppose
x = 2 as x ≤ 2 and
y = 3 as y ≤ 3
so
(2 x - 3 y) = (2*2 – 3*3)
= (4-9)
= (-5)
So ans is (2 x - 3 y) < -4

But the answer given is (2 x – 3 y) ≥ -4 HOW
 
if -1 ≤ x ≤ 2 and 1 ≤ y ≤ 3 then least positive value of (2y -3x) is

suppose
x = 2 as x ≤ 2 and
y = 3 as y ≤ 3
so
(2 x - 3 y) = (2*2 – 3*3)
= (4-9)
= (-5)
So ans is (2 x - 3 y) < -4

But the answer given is (2 x – 3 y) ≥ -4 HOW

You are talking about the least POSITIVE value of (2y-3x) - yet you are saying (2 x – 3 y) ≥ -4

How can "least positive value" be a negative number?

Make sure that you posted the problem correctly and you are looking at the correct answer!
 
if -1 ≤ x ≤ 2 and 1 ≤ y ≤ 3 then least positive value of (2y -3x) is
But the answer given is (2 x – 3 y) ≥ -4 HOW

As stated the answer makes no sense. I suspect that you have miss-copied something.

From the given
\(\displaystyle -6\le -3x\le 3\\2\le 2y\le 6~~\) so \(\displaystyle ~~-4\le 2y-3x\le 9~.\)

Because when \(\displaystyle x=2~\&~y=3\) we have \(\displaystyle 2y-3x=0\) so there is no least positive value.
 
Top